2006
DOI: 10.1097/01.coc.0000239093.95769.b3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Regression of Enlarged Neck Lymph Nodes on Radiation Doses Received by Parotid Glands During Intensity-Modulated Radiotherapy for Head and Neck Cancer

Abstract: Excessive parotid gland doses secondary to the regression of enlarged neck nodes could be mitigated by replanning after 45 Gy. However, recontouring of large lymph nodes that regress during therapy has a risk of under-dosing extracapsular extension of lymph node metastases. Therefore, recontouring should be done with extreme caution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 14 publications
2
25
0
2
Order By: Relevance
“…Decreased coverage of the target volume and increased doses to critical structure might be the consequence. In treatment with intensity-modulated radiotherapy (IMRT), where sharp dose gradients between the target and organs at risk require high precision of treatment [10,15,[17][18][19], replanning has been demonstrated to compensate these adverse effects of tumor shrinkage [8,13]. In-room imaging with soft-tissue contrast will allow us to observe such changes during radiotherapy and select patients in whom replanning might be necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased coverage of the target volume and increased doses to critical structure might be the consequence. In treatment with intensity-modulated radiotherapy (IMRT), where sharp dose gradients between the target and organs at risk require high precision of treatment [10,15,[17][18][19], replanning has been demonstrated to compensate these adverse effects of tumor shrinkage [8,13]. In-room imaging with soft-tissue contrast will allow us to observe such changes during radiotherapy and select patients in whom replanning might be necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Robar et al [4] documented that both parotid glands showed a median translation of 0.85 mm per week, and glands shrank by 4.9% per week. In the study by Kuo et al [5], the lymph nodes in head and neck cancer underwent a volume reduction of more than 50% after 45 Gy of treatment, which may increase actual radiation doses to the parotid glands. These anatomical changes would probably cause overdose to the OARs and underdose to targets, which would negate the benefits of IMRT.…”
mentioning
confidence: 99%
“…Kuo et al 14 observed an outward movement of the parotid glands in the pretreatment CT images in 10 patients with head and neck cancer, pushed by enlarged neck lymph nodes. After 45 Gy of IMRT, nodal regression caused the parotid glands to shift inward into the high-dose area.…”
Section: -13mentioning
confidence: 99%